2022
DOI: 10.3389/fpsyt.2022.831089
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Association Between Urbanicity and Psychotic-Like Experiences in Pre-Adolescence: The Indirect Effect of Urban Exposures

Abstract: Urban living is a growing worldwide phenomenon with more than two-thirds of people expected to live in cities by 2050. Although there are many benefits to living in an urban environment, urbanicity has also been associated with deleterious health outcomes, including increased risk for psychotic outcomes particularly when the urban exposure occurs in pre-adolescence. However, the mechanisms underlying this association is unclear. Here, we utilize one-year follow-up data from a large (N=7,979), nationwide study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 93 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…However, studies specific to children and adolescents reported opposite effects, in that living in an urban area was associated with more PE in children [23 ▪ ] and adolescents [11 ▪ ,12 ▪ ,30 ▪ ], especially for boys [30 ▪ ]. Urbanicity appeared to be associated specifically with persistence of PE, but not its onset [23 ▪ ].…”
Section: Effects Of Urbanization By Type Of Psychosismentioning
confidence: 90%
See 4 more Smart Citations
“…However, studies specific to children and adolescents reported opposite effects, in that living in an urban area was associated with more PE in children [23 ▪ ] and adolescents [11 ▪ ,12 ▪ ,30 ▪ ], especially for boys [30 ▪ ]. Urbanicity appeared to be associated specifically with persistence of PE, but not its onset [23 ▪ ].…”
Section: Effects Of Urbanization By Type Of Psychosismentioning
confidence: 90%
“…Specifically, residents in slum and semi-urban areas were observed to have worse outcomes (higher incidence and more progression of PE) when compared to residents from urban areas [36 ▪ ]. However, studies specific to children and adolescents reported opposite effects, in that living in an urban area was associated with more PE in children [23 ▪ ] and adolescents [11 ▪ ,12 ▪ ,30 ▪ ], especially for boys [30 ▪ ]. Urbanicity appeared to be associated specifically with persistence of PE, but not its onset [23 ▪ ].…”
Section: Effects Of Urbanization By Type Of Psychosismentioning
confidence: 91%
See 3 more Smart Citations